Toxoplasma gondii: Cellular aspects of parasite (Research, Society and Development, 2025)
Objective: Toxoplasma gondii is an obligate intracellular protozoan of significant veterinary and medical concern, as it causes toxoplasmosis, a disease that is easily transmissible and presents in various infectious forms. This review aims to explore the complexities of T. gondii transmission and pathogenesis, as well as the challenges in developing effective vaccines. Methodology: To produce the article, a literature review was carried out based on books and experimental papers through searches in Google, academic databases and PubMed. Impact: Toxoplasmosis remains a widespread public health and veterinary issue, particularly in immunocompromised individuals, where the disease can lead to more severe outcomes. We highlight comprehensive analysis of T. gondii’s life cycle, transmission routes, and mechanisms of host infection is presented. The review focuses on the parasite's ability to invade nucleated cells in the intermediate host, such as macrophages, epithelial cells, and neural and muscle cells, ultimately leading to the formation of cysts that contribute to chronic infection. Despite numerous studies on the parasite, the lack of an effective vaccine continues to hinder progress in disease prevention and control. Findings and Unique Contributions: This review highlights the sophisticated mechanisms by which T. gondii infects host cells and the chronicity of the disease through cyst formation. It emphasizes the ongoing gap in vaccine development, underscoring the urgent need for innovative approaches to vaccine design. The study offers a critical perspective on the current understanding of T. gondii biology and challenges in creating lasting immunity against toxoplasmosis, making it a valuable contribution to the field.